Efektifitas Minyak Kenanga (Cananga Odorata) sebagai Agen Deparafinisasi pada Pewarnaan Hematoxylin-Eosin - Putri, Gela Setya Ayu; Diyanah, Dina; Iswara, Arya (Jaringan Laboratorium Medis, 2024)
Histological staining usually requires deparaffinization before starting the staining process. Deparaffinization is a paraffin removal step that often uses a xylol solution. Deparaffinization with xylol has disadvantages, including being toxic, harmful to the human body, and hazardous to the environment. A safer alternative to xylol is required. Ylang-ylang oil, which contains β-caryophyllene, is non-polar and can be used as a substitute for xylol. This study aimed to compare the staining quality of guinea pig liver tissue slides with and without heating as a deparaffinization agent in hematoxylin-eosin (HE) staining. The research set up a quasi-experimental approach using samples of guinea pig liver tissue slides. The sample size was calculated using the Federer formula (n-1) (t-1) ≥ 15, resulting in a total sample of 27 slides divided into three treatment groups: xylol, ylang-ylang oil with and without heating. The Kruskal-Wallis test was used to examine the data. The quality staining of guinea pig liver slides deparaffinized with xylol was 100% good, and deparaffinization of ylang-ylang oil with heating was 100% good, whereas deparaffinization with ylang-ylang oil without heating was 11.1% less good, and the quality was good with an 88.9%. The normality test indicated that the data were not normally distributed (p0.05). The Kruskal-Wallis test was then used.